2020
DOI: 10.3390/foods9040398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Extraction Techniques for the Determination of Volatile Flavor Components in Broccoli

Abstract: To analyze aroma active components in a food product, the crucial step is to select a suitable extraction technique. It should provide isolation of all components responsible for aroma creation, without the formation of any artifacts during the procedure. Preferably, the extraction method should yield analyzed compounds in detectable levels. The presented study aimed to compare three popular extraction techniques used in flavor studies: solid-phase microextraction (SPME), solvent-assisted flavor evaporation (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…The present research showed how complex broccoli's aroma is and how many compounds from different chemical groups participate in its creation. Comparing results presented in this paper with earlier described research concerning aroma-active compounds in broccoli,10 the differences in the composition of odorants between broccoli varieties were noticeable, such as the absence of compounds like nonenal or 2,4-decadienal in the extract. Some analytical aspects related to techniques applied to identify compounds of interest need discussion.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The present research showed how complex broccoli's aroma is and how many compounds from different chemical groups participate in its creation. Comparing results presented in this paper with earlier described research concerning aroma-active compounds in broccoli,10 the differences in the composition of odorants between broccoli varieties were noticeable, such as the absence of compounds like nonenal or 2,4-decadienal in the extract. Some analytical aspects related to techniques applied to identify compounds of interest need discussion.…”
supporting
confidence: 79%
“…However, in the mentioned study, a different extraction technique was used-Solid phase microextraction (SPME) and volatile profile differ between exhaustive extraction and SPME techniques. 10 The analysis of cooked broccoli aroma showed that the number of odorants decreased drastically. Only 9 substances were noted after the GC-O analysis of the SAFE extract.…”
Section: Aroma Compounds In Cooked Broccolimentioning
confidence: 99%
See 1 more Smart Citation
“…Data acquisition was performed in the full scan mode from mass-to-charge ( m / z ) 35 to 300 with a scan time of 0.5 s with a total run time of 13 min. Retention indices (RI) of the compounds were determined by comparing the retention times of a homologous series of normal alkanes and then calculated as described by van Den Dool and Kratz [ 19 ]. Identification of metabolites was performed by matching mass spectra and retention indices to data in the literature and the National Institute of Standards and Technology (NIST08) spectral library.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, GC × GC/TOFMS is expected to provide more reliable variety identification (Rocha et al, 2013), variety classification (Dugo et al, 2014) and food quality control (Costa et al, 2015), and because of the existence of two retention mechanisms, a pattern of highly structural words is generally available. Now GC × GC/TOFMS has been successfully applied to the analysis of volatile flavor components in different food matrices, such as tea (Chen et al, 2019), wine (Šuklje et al, 2019), baijiu (Song et al, 2020), huangjiu (Zhou et al, 2019), broccoli (Wieczorek et al, 2020), oil (Chiara et al, 2015, vegetables (Wieczorek & Jelen´, 2019) and balsamic vinegar (Zhou et al, 2017), etc.…”
Section: Introductionmentioning
confidence: 99%